Narrative language competence in children and adolescents with Down syndrome - Channell, Marie Moore; McDuffie, Andrea S.; Bullard, Lauren M.; Abbeduto, Leonard (Frontiers in Behavioral Neuroscience, 2015)
This study was designed to examine the narrative language abilities of children and adolescents with Down syndrome (DS) in comparison to same-age peers with fragile X syndrome (FXS) and younger typically developing (TD) children matched by nonverbal cognitive ability levels. Participants produced narrative retells from a wordless picture book. Narratives were analyzed at the macrostructural (i.e., their internal episodic structure) and the microstructural (i.e., rate of use of specific word categories) levels. Mean length of utterance (MLU), a microstructural metric of syntactic complexity, was used as a control variable. Participants with DS produced fewer episodic elements in their narratives (i.e., their narratives were less fully realized) than the TD participants, although MLU differences accounted for the macrostructural differences between participant groups. At the microstructural level, participants with DS displayed a lower rate of verb use than the groups with FXS and typical development, even after accounting for MLU. These findings reflect both similarities and differences between individuals with DS or FXS and contribute to our understanding of the language phenotype of DS. Implications for interventions to promote language development and academic achievement are discussed.